THE ROLE OF FINANCIAL REPORTS IN IMPROVING THE QUALITY OF BANKING SERVICE: AN APPLIED STUDY IN RAFIDAIN BANK / TIKRIT - Eng.HAMAD ABED MUSTAFA; Eng. Emad Nayef Turki; Eng. Saad Sabbar Nasif (Scholar Express Journals, 2022)
The main objective of the research was to know the role of financial reports in improving the quality of banking service by applying to Rafidain Bank, Tikrit branch, where the descriptive analytical approach was relied, while the statistical software package for social sciences (SPSS) was relied on to process the data obtained from the research sample(49) individuals. According to the statistical treatment, the validity of the study’s furniture was determined by the presence of a significant statistically significant effect of financial reports on improving the quality of banking service, as well as the existence of a statistically significant correlation between financial reports as an independent variable and the quality of banking service as a reliable variable.
Keywords: Financial Reports; Quality; Banking Service.